Zagrożenia zdrowia mieszkańców wsi, w tym dzieci, w kontekście prac wykonywanych w gospodarstwie rolnym = Threats to the health of villagers, including children, in the context of the work carried out on the farm - Ciechańska, Beata; Olejniczak, Dominik; Skonieczna, Joanna; Dykowska, Grażyna (Journal of Education, Health and Sport, 2016)
Ciechańska Beata, Olejniczak Dominik, Skonieczna Joanna, Dykowska Grażyna. Zagrożenia zdrowia mieszkańców wsi, w tym dzieci, w kontekście prac wykonywanych w gospodarstwie rolnym = Threats to the health of villagers, including children, in the context of the work carried out on the farm. Journal of Education, Health and Sport. 2016;6(4):181-192. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50070 http://ojs.ukw.edu.pl/index.php/johs/article/view/3462 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. Zagrożenia zdrowia mieszkańców wsi, w tym dzieci, w kontekście prac wykonywanych w gospodarstwie rolnym Threats to the health of villagers, including children, in the context of the work carried out on the farm Beata Ciechańska1, Dominik Olejniczak2, Joanna Skonieczna2, Grażyna Dykowska2 1Studenckie Koło Naukowe Zdrowia Publicznego, sekcja Promocji Zdrowia, Warszawski Uniwersytet Medyczny 2Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny Słowa kluczowe: zagrożenia zdrowia, środowiskowe uwarunkowania zdrowia, ludność wiejska. Key words: health threats, health determinants, rural population. lic zdr. publ. Beata Ciechańska1 dr n. med. Dominik Olejniczak2 mgr Joanna Skonieczna2 dr n. o zdr. Grażyna Dykowska2 Streszczenie Stopień narażenia na choroby i urazy wśród ludności wiejskiej jest inny, niż w przypadku mieszkańców miast. Wynika to z uwarunkowań środowiskowych, a także ze specyfiki pracy. Wart podkreślenia jest fakt, iż, nadal duża liczba dzieci narażona jest na uszczerbek na zdrowiu w wyniku angażowania ich do prac niebezpiecznych lub przekraczających ich możliwości. W 2012 roku 168 mln dzieci na świecie wykonywało pracę, a 85 mln dzieci angażowanych było do prac niebezpiecznych. Gałęzią działalności gospodarczej, w której najczęściej pracują dzieci, jest rolnictwo [1]. W Polsce praca dzieci w rodzinnym gospodarstwie rolnym jest społecznie akceptowalna. Pomimo, iż udział dzieci w tych zajęciach niewątpliwie może mieć pozytywny wpływ na ich zdrowie praca na wsi często wiąże się z licznymi groźnymi dla zdrowia i życia urazami. Istnieje szereg instytucji, które prowadzą działania, mające na celu zminimalizowanie ryzyka zdrowotnego wśród mieszkańców wsi. Działania te polegają między innymi na realizowaniu programów zdrowotnych, opartych na edukacji. Te inicjatywy, choć słuszne, wymagają jednak zintensyfikowania, by objąć swoim zasięgiem jak największą grupę ludności wiejskiej, szczególnie dzieci i młodzieży. Threats to the health of villagers, including children, in the context of the work carried out on the farm Abstract The degree of exposure to disease and injuries among the rural population is different in the case of urban residents. This is due to environmental conditions, as well as the specifics of the work. It is worth emphasizing that, still a large number of children are exposed to bodily harm as a result of engaging their use for dangerous work or exceeding their capabilities. In 2012, 168 million children worldwide involved in jobs, and 85 million children were involved hazardous work. Branch of economic activity in which children usually work, is agriculture. [1] In Poland, the work of children in a family farm is socially acceptable. Although the share of children in these classes can undoubtedly have a positive impact on their health work in the countryside it is often associated with numerous dangerous to life and limb injuries. There are a number of institutions that carry out activities aimed at minimizing health risks among the villagers. These measures consist, inter alia, implementation of health programs based on education. These initiatives, though correct, however, intensify the need to embrace its reach as the largest group of rural population, especially children and adolescents.